A unique coexistence of a plurihormonal pituitary adenoma with granulomatous hypophysitis - Sanjiban Patra; Priti Trivedi (Indian Journal of Pathology and Microbiology)
Dual pathology in the pituitary gland is a unique phenomenon. Coexistence of a pituitary adenoma with primary hypophysitis has been reported rarely with very few cases in the literature. Among the primary hypophysitis, primary granulomatous subtype has been proposed to be idiopathic and autoimmune in nature. Plurihormonal pituitary adenomas produce hormones of more than one different pituitary cell lineage. Pituitary adenoma with a single hormonal content has been documented with concurrent primary granulomatous hypophysitis. The present case describes the unique coexistence of a plurihormonal adenoma showing somatotroph, lactotroph, and corticotroph lineage with primary granulomatous inflammation in the sellar region in a 36-year-old woman.